Energy exchange via multi-species streaming in laser-driven ion acceleration. (18th October 2016) - King, M; Gray, R J; Powell, H W; Capdessus, R; McKenna, P
Abstract: Due to the complex electron dynamics and multiple ion acceleration mechanisms that can take place in the interaction of an ultra-intense laser pulse with a thin foil, it is possible for multiple charged particle populations to overlap in space with varying momentum distributions. In certain scenarios this can drive streaming instabilities such as the relativistic Buneman instability and the ion–ion acoustic instability. The potential for such instabilities to occur are demonstrated using particle-in-cell simulations. It is shown that if a population of ions can be accelerated such that it can propagate through other slowly expanding ion populations, energy exchange can occur via the ion–ion acoustic instability.